(untitled) (Canadian Journal of Native Studies, 2026)
This study investigated the demographic and academic factors associated with academic progression of Indigenous first-year students at the University of Manitoba. Student demographics and measured academic factors were highly associated with degree progression. First-year students who did not return were more likely to be male, at least 21 years of age, had not completed high school, and members of First Nations. These results have implications for policy and student supports, and universities must work closely with Indigenous stakeholders to prepare and support Indigenous leaners, remove policy barriers, and address the need for changes to university culture and curriculum.